The Influence of Intellectual Capital and Corporate Social Responsibility on Financial Performance and Company Value: Pengaruh Intellectual Capital dan Corporate Social Responsibility Terhadap Kinerja Keuangan dan Nilai Perusahaan - Sholikhah, Alfiyatus; Hermawan, Sigit (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to examine the effect of Intellectual Capital and Corporate Social Responsibility on Financial Performance and Firm Value (Study on Banking and Insurance Companies Listed on the Indonesia Stock Exchange in 2016-2019). The variables studied in this study were Intellectual Capital, Corporate Social Responsibility, Financial Performance, and Company Value. The type of research used in this research is quantitative. This study uses secondary data from the financial statements of banking and insurance companies (annual reports) listed on the Indonesia Stock Exchange in 2016-2019. The analytical method used is using multiple linear regression analysis with the help of the SPSS 26 program. The results of this study indicate that (1) Intellectual Capital has no effect on Financial Performance (2) Intellectual Capital has no effect on Firm Value (3) Corporate Social Responsibility has no effect on Financial Performance (4) Corporate Social Responsibility has no effect on Firm Value.